Determinants of Physical Activity Participation following Traumatic Brain Injury - Reavenall, Sarah (2009)
Background Research concerning physical activity participation in the Traumatic Brain Injury (TBI) population is limited. There is a need for investigation into barriers and facilitators to exercise faced by individuals with TBI.